A preliminary validity study of the Rathus Assertiveness Schedule with a sample of the South African university population - Dares, Anna Ewa (Rhodes University, Faculty of Humanities, Department of Psychology, 1981)
The study investigated the validity of the Rathus Assertiveness Schedule (RAS) with a sample (N=l68) of the white South African undergraduate students. In terms of criterion- related validity, results indicated that ratings of external judges, unaware of their subjects' self-evaluation, correlated significantly with the assertiveness scores of the male subjects only. Construct validation of the RAS with ten personality traits measured by the Howarth Personality Questionnaire yielded results consistent with Wolpe's hypothesis that assertiveness relates inversely to anxiety. In addition, evidence was found to support the contention that assertiveness correlates negatively with inferiority. A principal components analysis of the RAS revealed a potentially useful factor structure for both males and females. A number of factors including situation-specific assertive behavior as well as factors measuring aggressiveness were identified for both sexes.
Keywords: Uncatalogued